Sustained home visiting for vulnerable families and children: a review of effective processes and strategies - Anna Price
Parenting young children has become a more complex and stressful business, especially for those families in our community with the least resources (Grose, 2006; Hayes et al, 2010; Poole, 2004; Richardson & Prior, 2005; Trask, 2010). A widening gap exists between families that function well and those that are vulnerable. The paradox of service delivery for children and families is that vulnerable families – that is, those families with the greatest needs – are also the least likely to be able to access those services (Ghate & Hazel, 2002; Fram, 2003). A range of barriers exist for vulnerable and at risk families in making use of services (Carbone et al, 2004). One of the key barriers to vulnerable families accessing services is that many find it difficult to relate to the formal service system and are easily alienated by practices others find acceptable. Research regarding parents’ experiences of support services suggests that parents want services where they are simultaneously cared for and enabled in their role as parents, and to receive services characterised by empathy, competence, functionality, respect, flexibility and honesty (Attride-Stirling et al, 2001; Winkworth et al, 2009). Vulnerable parents fear a loss of autonomy in their interactions with support services and want services that are non-judgemental and that provide continuity of care (Ghate & Hazel, 2002; von Bultzingslowen, 2006). In addition to the barriers faced by vulnerable and marginalised families in accessing services, the system does not work in an integrated or coherent fashion to ensure that all children and families needing support receive it. Furthermore, the vast majority of services for children and families in Australia do not have an outreach function, that is, a means of engaging these vulnerable and at risk families who are in need of support but use services inconsistently or not at all. In short, the service system was not designed to meet the needs of vulnerable families within the context of a rapidly changing social and economic climate. Therefore, many families requiring support are not receiving it. Related identifier: ISSN 2204-340